Proses Perdagangan Manusia dalam Film Trade of Innocents - Ariel Vieri Guliani; Nungki Heriyati (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
Film has a purpose to convey a story idea in the form of moviing images. to create an interesting story idea, the use of cinematography aspects used to show how a story tells in visual moving images. In the film Trade of Innocents (2012) tells the story of the process of human trafficking children undearge that occurs in Cambodia. The purpose of analysis to discover the process of human trafficking. The method used in this article is qualitative method. The data used in this analysis is scenes image on Trade of Innocents film which can be accessed on Prime Video application. The object of analysis focuses on the process of human trafficking in the film. The result of research process of human trafficking found in two stages. First, it show how the process of recruiting victims by directly abduction or buying the victim from family themself. Second, show how the process of selling victim of human trafficking in brothel house start from offering the victim to the customer then sell them after the customer do payment to the human trafficker. In that case, the victim of human trafficking get exploitation by forced labour in world of prostitution. Keywords: Victim, Process of Recruitment Human Trafficking, Exploitation